(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This work analysis the value of active learning methodologies when these are distributed by educational networks. If these add value and improve the quality ofteaching-learning process in EHEA. So, It was started a teaching innovation projectduring the academic year 2011/2012. To do it we made multimedia tools to get results of an opinion poll among students. The statistical population under studywas the students of a subject of Second Course of the Degree of Tourism: “Financial Accounting”. Multimedia tools were distributed by the platform ALF. ALF supportsthe e-learning of the degree courses.